The effect of feeding pre-starter on performance efficiency of local chicken (KUB chicken) - Sofjan Iskandar; Cecep Hidayat; T. Cahyaningsih (Indonesian Center for Animal Research and Development (ICARD), 2014)
An experiment in feeding pre-starter diets was carried out on local chicken (KUB chicken) raised to the age of 84 days. Four hundred and eighty day-old KUB chicks were allocated to experimental diets of P1 = standard diet without pre-starter; P2 = OASIS® pre-starter for 48 hours feeding; P3 = COBA-1, a mixture of 76.3% yolk powder, 0.76% inulin powder, 7.63 % honey and 15.3% tomato sauce, for 24 hours feeding; P4 = P3 given for 48 hours feeding; P5 = fresh papaya for 24 hours feeding; P6 = P5 for 48 hours feeding; P7 = fasting for 24 hours and P8 = fasting for 48 hours. Following treatment, the chicks were then fed with standard diet, containing 17.5 % crude protein with 2800 kcal ME/kg up to the end of the experiment. Results showed that the group of chicken on pre-starter diet of ripe papaya fruit (P5 and P6), responded better EPEF (European Performance Efficiency Factor) value of 442 and 356 g/bird, respectively in chicken of P5 and P6. This better response was due to particularly higher viability and the efficiency in utilization of feed.